Palladium-based composite membranes comprising a silicoaluminophosphate molecular sieve, methods of making the same, and use in carbon dioxide capture
By preparing a palladium-based composite membrane supported on a silicon-aluminum molecular sieve, the problems of low carbon dioxide recovery rate and insufficient hydrogen purity in carbon dioxide pre-combustion capture technology were solved, achieving efficient carbon dioxide capture and high-purity hydrogen separation, reducing energy consumption and enhancing membrane stability.
Patent Information
- Application Number
- CN202210841761.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-18
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2042-07-18
AI Technical Summary
Existing carbon dioxide pre-combustion capture technologies suffer from low carbon dioxide recovery rates, insufficient hydrogen product purity, and high energy consumption. In particular, in integrated coal gasification combined cycle power generation systems, equipment corrosion is severe, and operation and maintenance costs are high.
A palladium-based composite membrane, including a silica-alumina molecular sieve, is used for carbon dioxide capture. The membrane is composed of a composite palladium-based alloy material and a silica-alumina molecular sieve loaded with sodium-modified nano-Fe3O4. It is prepared through alloying treatment and hydrothermal crystallization.
It achieves efficient carbon dioxide capture and high-purity hydrogen separation, reduces energy consumption, improves hydrogen purity, and enhances membrane stability and resistance to carbon buildup, making it suitable for coal gasification combined cycle power generation and natural gas combined cycle power generation.
Smart Images

Figure CN117443210B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of palladium-based alloy materials, specifically to a palladium-based composite membrane comprising a silicon-aluminum molecular sieve, its preparation method, and its application in carbon dioxide capture. Background Technology
[0002] Carbon capture, use, and sequestration (CCUS) is a technology with significant potential for large-scale greenhouse gas emission reduction and is an important technological option for mitigating CO2 emissions in the future. Research by the International Energy Agency (IEA) indicates that applying CCUS technology is a necessary emission reduction measure in addition to improving energy system efficiency and replacing fossil fuels with nuclear and renewable energy, and its emission reduction contribution will increase year by year. It is projected that by 2050, emission reductions achievable through CCUS technology will account for 17% of total emission reductions. Given my country's coal-dominated energy structure, developing CCUS technology can effectively control greenhouse gas emissions and simultaneously promote the transformation and upgrading of the power industry. Power systems have concentrated emission sources and high CO2 emission intensity. Therefore, CO2 capture at power plants is one of the most effective ways to achieve carbon emission reduction and is also one of the most challenging technological aspects of current CCUS development. CO2 capture technologies based on power generation systems are mainly divided into three categories: post-combustion capture, pre-combustion capture, and oxy-fuel combustion. Significant progress has been made in the development of CO2 capture technology worldwide. The biggest problem at present is the high cost and energy consumption of capture, which is also the focus of current technological research and development.
[0003] Pre-combustion carbon capture technology refers to the process of transferring chemical energy from carbon-based fuels before combustion, and then separating the carbon from other energy-carrying substances to achieve carbon capture before combustion. Integrated gasification combined cycle (IGCC) power generation is the most typical system capable of pre-combustion carbon capture. IGCC is a power generation system that combines coal gasification with a combined cycle of gas and steam. Fossil fuels are gasified into syngas (mainly composed of CO and H2), and then the CO2 concentration is increased using a water-gas shift reaction. The hydrogen-rich gas obtained after CO2 capture can be used for combustion power generation, and the separated CO2 can be compressed and purified for further utilization or storage.
[0004] Current carbon dioxide pre-combustion capture technologies mainly employ adsorption-flash evaporation-recompression processes. Their main drawbacks include complex processes, high energy consumption, large reaction mass transfer resistance, low carbon dioxide recovery efficiency, insufficient purity of the separated hydrogen, and low efficiency in subsequent combustion power generation. Furthermore, the use of alkaline adsorbents causes significant corrosion to the equipment, increasing overall operating and maintenance costs. Summary of the Invention
[0005] The purpose of this invention is to overcome the problems of low carbon dioxide recovery rate and insufficient hydrogen product purity in the prior art, and to provide a palladium-based composite membrane including a silicon-aluminum molecular sieve, its preparation method and its application in carbon dioxide capture.
[0006] To achieve the above objectives, the first aspect of the present invention provides a palladium-based composite membrane comprising a silicon-aluminum molecular sieve. The composite membrane comprises a composite palladium-based alloy material and a silicon-aluminum molecular sieve loaded with sodium-modified nano-Fe3O4 attached to the surface of the composite palladium-based alloy material. The composite palladium-based alloy material contains Pd, Cu, and Ag, and the molar ratio of Pd, Cu, and Ag is 100:(12-38):(9-25). The crystal structure of the composite palladium-based alloy material is face-centered cubic close-packed, and the lattice parameter k is 0.4025-4255 nm.
[0007] A second aspect of the present invention provides a method for preparing a palladium-based composite membrane comprising a silica-alumina molecular sieve, the method comprising:
[0008] (1) Pd, Cu and Ag are deposited on the support, and then the support with Pd, Cu and Ag deposited is alloyed, wherein the molar ratio of Pd, Cu and Ag is 100:(12-38):(9-25).
[0009] The alloying process is as follows: in an activating atmosphere, heat treatment is first performed at a temperature of 500-650°C and a pressure greater than 0.1 MPa, and then the temperature is reduced to below 200°C at a rate greater than 30°C / min. The gas providing the activating atmosphere may optionally include an alkaline gas.
[0010] (2) The alloyed material is placed in a solution of a precursor containing silicon-aluminum molecular sieve and subjected to hydrothermal crystallization, drying and calcination in sequence to obtain a composite membrane precursor.
[0011] (3) Sodium-modified nano-Fe3O4 is loaded onto the surface of the composite membrane precursor.
[0012] A third aspect of the present invention provides a composite membrane prepared by the method described above.
[0013] A fourth aspect of the present invention provides a composite palladium-based alloy material, which is the composite palladium-based alloy material defined above or the product of the alloying treatment described above.
[0014] The fifth aspect of the present invention provides an application of the above-described composite membrane in carbon dioxide capture.
[0015] The composite palladium-based alloy material of this invention exhibits low hydrogen permeation activation energy, high hydrogen permeation efficiency, stability, and resistance to carbon deposition; the prepared composite membrane possesses low hydrogen permeation activation energy, high hydrogen and nitrogen selectivity, and long service life. The composite palladium-based alloy material or composite membrane of this invention is particularly suitable for carbon dioxide capture.
[0016] Furthermore, this invention applies low-power membrane separation technology to the pre-combustion capture process of carbon dioxide, obtaining high-purity hydrogen while enriching carbon dioxide for subsequent power generation, fuel cell systems, or other energy conversion methods. For the mixture of CO2 and a portion of H2 obtained on the permeate side, carbon dioxide enrichment and storage or carbon dioxide hydrogenation to produce gasoline distillate hydrocarbons can be selectively carried out based on the mixture's composition. Compared to existing technologies, this invention's capture and utilization of carbon dioxide occurs in the fields of coal gasification combined cycle power generation and natural gas combined cycle power generation. On the one hand, this invention can additionally provide high-quality hydrogen products with a purity >99.99% for use in various hydrogen utilization fields such as combustion power generation, fuel cells, and hydrogen refueling stations; on the other hand, it can convert carbon dioxide into high-value-added gasoline distillate hydrocarbons, improving the overall utilization rate of carbon dioxide; and thirdly, the entire process requires no external energy input, significantly reducing energy consumption. Attached Figure Description
[0017] Figure 1 This is a schematic diagram of a composite membrane encapsulated and placed in a tubular reactor.
[0018] Figure 2 This is the characteristic X-ray diffraction (XRD) spectrum of the HZSM-5 molecular sieve structure;
[0019] Figure 3 This is a scanning electron microscope (SEM) image of Na-modified Fe3O4 nanoparticles. Detailed Implementation
[0020] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0021] The first aspect of the present invention provides a palladium-based composite membrane comprising a silicon-aluminum molecular sieve, the composite membrane comprising a composite palladium-based alloy material and a silicon-aluminum molecular sieve loaded with sodium-modified nano-Fe3O4 attached to the surface of the composite palladium-based alloy material (i.e., sodium-modified nano-Fe3O4 loaded on the silicon-aluminum molecular sieve), wherein the composite palladium-based alloy material contains Pd, Cu and Ag, and the molar ratio of Pd, Cu and Ag is 100:(12-38):(9-25), and the crystal structure of the composite palladium-based alloy material is face-centered cubic close-packed with a lattice parameter k of 0.4025-4255 nm.
[0022] In this invention, "face-centered cubic close packing" means that the 14 atoms involved in a unit cell belong to 4 layers: with one vertex as layer A, the three face-centered atoms and three vertex atoms adjacent to it belong to layer B, the next 6 atoms belong to layer C, and there is another vertex opposite to the vertex of layer A, which is in the next cycle of layer A.
[0023] In this invention, "lattice parameter k" refers to the physical dimensions of a unit cell in a crystal lattice, representing a fundamental structural parameter of a crystalline material. The lattice parameter k represents the edge length of the unit cell, that is, the edge length of each parallelepiped unit, and it is directly related to the bonding energy between atoms. A unit cell in three-dimensional space generally has three lattice parameters, denoted by a, b, and c. Based on the morphological distribution of the Bravais lattice, in the cubic crystal structure (face-centered cubic close packing) involved in this invention, these three constants are all equal, and therefore can be represented by parameter k. Changes in k reflect changes in the composition, stress state, etc., within the crystal. The lattice parameter k can be determined using X-ray diffraction (XRD) and atomic force microscopy (AFM).
[0024] According to the present invention, preferably, the half-width at half-maximum (WHM) of at least one characteristic peak of 2θ in the range of 10°-90° in the XRD pattern of the composite palladium-based alloy material is less than or equal to 0.1633; more preferably, the WHM of all characteristic peaks of 2θ in the range of 10°-90° in the XRD pattern of the composite palladium-based alloy material is less than or equal to 0.1633, more preferably less than or equal to 0.084 or less than or equal to 0.078 or less than or equal to 0.072 or less than or equal to 0.069 or less than or equal to 0.064 or less than or equal to 0.055 or less than or equal to 0.039, and generally greater than or equal to 0.052 or greater than or equal to 0.059 or greater than or equal to 0.062 or greater than or equal to 0.068 or greater than or equal to 0.073; further preferably, the composite palladium-based alloy material In the XRD pattern of the material, the half-width at half-maximum (WHM) of the characteristic peak at 2θ = 40° ± 1° (i.e., the characteristic peak of crystal plane (110)) is less than or equal to 0.0698 or 0.055, or the half-width at half-maximum (WHM) of the characteristic peak at 2θ = 46° ± 1° (i.e., the characteristic peak of crystal plane (111)) is less than or equal to 0.0873 or 0.069, or the half-width at half-maximum (WHM) of the characteristic peak at 2θ = 69° ± 1° (i.e., the characteristic peak of crystal plane (220)) is less than or equal to 0.1047 or 0.072, or the half-width at half-maximum (WHM) of the characteristic peak at 2θ = 83° ± 1° (i.e., the characteristic peak of crystal plane (311)) is less than or equal to 0.1396 or 0.078, or the half-width at half-maximum (WHM) of the characteristic peak at 2θ = 87° ± 1° (i.e., the characteristic peak of crystal plane (222)) is less than or equal to 0.1633 or 0.084. The "half-maximum width" (HWHM) is defined as the width of the peak at half its height, i.e., the half-maximum width. It is converted to radians using the Debye-Scherrer formula (D = Kγ / Bcosθ), and the HWHM value is used to characterize the size of the peak. When the composite palladium-based alloy material has no characteristic peak at the corresponding 2θ position, the HWHM is considered to be 0.
[0025] According to the present invention, preferably, the thickness of the composite palladium-based alloy material is 0.5-30 μm, and more preferably 5-15 μm.
[0026] According to the present invention, preferably, the composite membrane is a tubular membrane.
[0027] According to the present invention, preferably, the composite membrane further includes a support, the composite palladium-based alloy material is attached to the support, and the thickness of the support is 0.1-20 mm, more preferably 2-5 mm.
[0028] According to the present invention, preferably, the silica-alumina molecular sieve is at least one of HZSM-5, HZSM-11, HZSM-12, HZSM-23, HZSM-34, HY, HMCM-22, HBEA and HMOR.
[0029] According to the present invention, preferably, the thickness of the silica-alumina molecular sieve loaded with sodium-modified nano-Fe3O4 is 100-3750 nm, more preferably 350-1500 nm.
[0030] According to the present invention, preferably, the silicon-aluminum molar ratio of the silica-alumina molecular sieve is (2-50):1, more preferably (5-20):1; the average particle size is 50-420 nm, more preferably 150-300 nm; the average pore size is 0.25-225 nm, more preferably 0.75-35 nm; and the specific surface area is 25-600 m². 2 / g, more preferably 50-500m 2 / g; crystallinity greater than or equal to 92%, more preferably 96-99%.
[0031] According to the present invention, preferably, the average particle size of the sodium-modified nano-Fe3O4 is 5-300 nm, more preferably 10-100 nm.
[0032] According to the present invention, preferably, the loading of the sodium-modified nano-Fe3O4 is such that the molar ratio of Pd to Fe is 1:(0.001-0.1), more preferably 1:(0.001-0.03).
[0033] According to the present invention, preferably, the molar ratio of Na to Fe in the sodium-modified nano Fe3O4 is 1:(1-10), more preferably 1:(3-6).
[0034] A second aspect of the present invention provides a method for preparing a palladium-based composite membrane comprising a silica-alumina molecular sieve, the method comprising:
[0035] (1) Pd, Cu and Ag are deposited on the support, and then the support with Pd, Cu and Ag deposited is alloyed, wherein the molar ratio of Pd, Cu and Ag is 100:(12-38):(9-25).
[0036] The alloying treatment is performed as follows: in an activating atmosphere, heat treatment is first carried out at a temperature of 500-650℃ (such as 500℃, 540℃, 550℃, 560℃, 570℃, 580℃, 590℃, 600℃ or any value between the above) and a pressure greater than 0.1MPa, and then the temperature is reduced to below 200℃ at a rate greater than 30℃ / min (such as 31, 35, 40, 45, 55, 65, 70, 80, 100℃ / min or any value between the above). The gas providing the activating atmosphere may optionally include an alkaline gas.
[0037] (2) The alloyed material is placed in a solution of a precursor containing silicon-aluminum molecular sieve and subjected to hydrothermal crystallization, drying and calcination in sequence to obtain a composite membrane precursor.
[0038] (3) Load (or deposit) sodium-modified nano-Fe3O4 on the surface of the composite membrane precursor.
[0039] According to the present invention, preferably, the alloying treatment is carried out by treating the material in an activating atmosphere at a temperature of 600-625°C and a pressure of 0.56-0.73 MPa for 1.5-7 hours, followed by cooling to 150-200°C at a rate of 55-75°C / min. The composite palladium-based composite membrane obtained according to this preferred embodiment has higher hydrogen permeability or stability.
[0040] In this invention, the gas providing the activating atmosphere can be any common gaseous gas in the art that is in a gaseous state under alloying conditions. Preferably, the activating atmosphere is provided by at least one of rare gases (such as Ar), N2, water vapor, H2, acidic gases (such as CO2), and basic gases (such as ethylenediamine and NH3, PH3, N2H4). According to a preferred embodiment of the invention, the gas providing the activating atmosphere includes hydrogen and nitrogen, wherein the hydrogen content in the mixture of hydrogen and nitrogen is greater than or equal to 30% by volume, more preferably 35-65% by volume. The addition of a basic gas enables faster activation of the palladium-based alloy film, resulting in a more stable face-centered cubic structure and a smaller full width at half maximum (FWHM) of the characteristic peaks in the XRD pattern. Therefore, preferably, the gas providing the activating atmosphere includes a basic gas.
[0041] According to a preferred embodiment of the invention, the gas providing the activating atmosphere includes hydrogen and an alkaline gas. More preferably, the content of the alkaline gas in the gas providing the activating atmosphere is greater than or equal to 20% by volume, such as 22% by volume, 25% by volume, 28% by volume, 30% by volume, 40% by volume, 50% by volume, or any value between the above values. Similar effects can be obtained by providing an activating atmosphere consisting solely of an alkaline gas.
[0042] According to the present invention, preferably, the alkaline gas is selected from at least one of ethylenediamine, NH3, PH3 (phosphine) and N2H4 (hydrazine).
[0043] In this invention, the pressure of the alloying process is generally controlled by adjusting the amount of gas used to provide the activating atmosphere. After being cooled to below 200°C at a specific rate, it can be cooled to room temperature for later use.
[0044] According to the present invention, preferably, the total thickness of Pd, Cu and Ag deposited on the support is 0.5-30 μm, more preferably 5-15 μm.
[0045] According to the present invention, preferably, the thickness of the support is 0.1-20 mm, more preferably 2-5 mm. The support can be provided by materials commonly used in the art that can withstand the operating temperature of the present invention without affecting hydrogen permeability, that is, materials that do not deform or affect hydrogen permeability at the operating temperature of the present invention. While ensuring excellent hydrogen permeability, to obtain better mechanical and thermal stability and reduce the amount of palladium used (reducing costs), preferably, the support is a porous support, which can be selected from at least one of porous ceramics, porous glass, porous metals (such as porous stainless steel), porous quartz, and polymers, more preferably from at least one of porous ceramics, porous metals, and polymers. Generally, the porosity distribution of the support ranges from 15-75%, and the average pore size is 0.05-0.4 μm. To obtain a tubular membrane, the support is preferably a tubular support. The porous ceramic material can be γ-Al₂O₃, with a porosity distribution range of 25-66% and an average pore size of 0.12-0.4 μm. Porous stainless steel can be made of 316L (Fe) 69 Cr 17 Ni 12 Mo2 has a porosity ranging from 32% to 71% and an average pore size of 0.08 to 0.36 μm. The polymer material can be polyimide, with a porosity ranging from 15% to 37% and an average pore size of 0.05 to 0.22 μm. The "porosity range" and "average pore size" can both be determined using nitrogen physical adsorption.
[0046] According to the present invention, preferably, the precursor solution of the silicon-aluminum molecular sieve contains a silicon source, an aluminum source, a template agent, and water.
[0047] According to the present invention, preferably, the molar ratio of the silicon source, aluminum source, template agent and water is 100:(2-50):(15-65):(60-2400), more preferably 100:(5-20):(20-50):(70-1250).
[0048] According to the present invention, preferably, the amount of the solution of the precursor containing silicon-aluminum molecular sieve is 0.025-0.85 ml relative to 1 g of alloyed material.
[0049] According to the present invention, the silicon source can be a substance commonly used in the art that can provide silicon. Preferably, the silicon source is at least one of silicate ester, silicate and silicon dioxide, more preferably selected from at least one of tetrabutyl orthosilicate, tetraethyl orthosilicate, sodium silicate, potassium silicate, silica sol and water glass.
[0050] According to the present invention, the aluminum source can be a substance commonly used in the art that can provide aluminum. Preferably, the aluminum source is at least one of aluminate, alumina, aluminum salt, aluminum sol and organic aluminum alkoxide, and more preferably at least one of sodium aluminate, boehmite, aluminum sulfate, aluminum nitrate and aluminum isopropoxide.
[0051] According to the present invention, preferably, the template agent is at least one selected from tetraalkylammonium hydroxide, alkylamine and tetraalkylammonium halide, more preferably selected from at least one selected from tetrabutylammonium hydroxide, tetrapropylammonium hydroxide, tetraethylammonium hydroxide, triethylamine, hexadecyltrimethylammonium bromide and isopropylamine.
[0052] According to the present invention, preferably, the hydrothermal crystallization method is to first perform aging and then crystallize.
[0053] Preferably, the aging conditions include an aging temperature of 70-90°C.
[0054] Preferably, the aging conditions further include an aging time of 6-10 hours.
[0055] Preferably, the crystallization conditions include a crystallization temperature of 160-190°C.
[0056] Preferably, the crystallization conditions further include a crystallization time of 24-48 hours.
[0057] The aging process of the present invention can be carried out under stirring conditions, preferably at a stirring rate of 800-1000 rpm. The crystallization process of the present invention can also be carried out under stirring conditions, preferably at a stirring rate of 15-30 rpm.
[0058] According to the present invention, there are no special requirements for the drying conditions. Preferably, the drying conditions include: a drying temperature of 50-80°C and a drying time of 8-12 hours.
[0059] According to the present invention, preferably, the calcination conditions include a calcination temperature of 575-625°C.
[0060] According to the present invention, preferably, the calcination conditions further include a calcination time of 4-6 hours.
[0061] According to the present invention, when the silicon source and / or aluminum source (such as sodium silicate, potassium silicate, water glass, sodium aluminate) contains Na or K, the product after calcination is a sodium-type molecular sieve. Therefore, in order to obtain a hydrogen-type molecular sieve, the method preferably further includes ammonium exchange of the calcined product. Conventional methods can be used for ammonium exchange, which will not be described in detail here.
[0062] According to the present invention, preferably, the method of depositing sodium-modified nano-Fe3O4 on the surface of the composite membrane precursor is as follows: impregnating the composite membrane precursor with a solution containing an iron source and a sodium source, and then drying and calcining it in sequence, wherein the molar ratio of Na to Fe in the solution containing the iron source and the sodium source is 1:(1-10).
[0063] According to the present invention, the concentration of Fe in the solution containing iron and sodium sources can be 0.01-0.86 mol / L;
[0064] According to the present invention, the concentration of Na in the solution containing iron and sodium sources can be 0.01-0.55 mol / L.
[0065] According to the present invention, preferably, the amount of solution containing iron source and sodium source is 0.01-0.05 ml relative to 1 g of composite membrane precursor.
[0066] According to the present invention, the iron source can be a substance commonly used in the art that can provide iron. Preferably, the iron source is selected from at least one of ferric salts and ferrous salts, more preferably from at least one of FeCl3, FeCl2, Fe(NO3)3, FeSO4, NH4Fe(SO4)2, and (NH4)2Fe(SO4)2. According to a particularly preferred embodiment, the iron source is a molar ratio of ferric ions (Fe2+) of 1.5-2.5. 3+ ) source (such as FeCl3) and ferrous ions (Fe 2+ Source (such as FeCl2).
[0067] According to the present invention, the sodium source can be a substance commonly used in the art that can provide sodium. Preferably, the sodium source is selected from at least one of sodium hydroxide and sodium salts, and more preferably from at least one of NaOH, NaHCO3, Na2CO3 and NaCl.
[0068] According to the present invention, preferably, the pH value of the solution containing the iron source and the sodium source can be 8-12, more preferably 9-11. When using NaOH as the sodium source, the content of NaOH in the solution is preferably such that the pH value of the solution meets the above-mentioned range.
[0069] According to the present invention, preferably, the impregnation conditions include: an impregnation temperature of 15-85°C, more preferably 25-60°C; and an impregnation time of 0.5-3.5 h, more preferably 1-2 h.
[0070] According to the present invention, preferably, the calcination conditions include: a calcination temperature of 325-500℃ and a calcination time of 3-5h.
[0071] According to the present invention, preferably, before impregnating the composite membrane precursor with a solution containing iron and sodium sources, the solution containing iron and sodium sources is aged, and the aging conditions include: a temperature of 20-70°C and a time of 0.5-3h.
[0072] A third aspect of the present invention provides a composite membrane prepared by the method described above.
[0073] A fourth aspect of the present invention provides a composite palladium-based alloy material, which is the composite palladium-based alloy material defined above or the product of the alloying treatment described above.
[0074] The fifth aspect of this invention provides an application of the aforementioned composite membrane in carbon dioxide capture. Specific steps for capturing carbon dioxide using the composite membrane may include: subjecting a feed gas containing carbon dioxide and hydrogen to a carbon dioxide hydrogenation reaction in the presence of a sodium-modified nano-Fe3O4-supported aluminosilicate molecular sieve to produce gasoline-grade hydrocarbon fractions; purifying the unreacted hydrogen gas to over 99.999% by sequentially passing it through the sodium-modified nano-Fe3O4-supported aluminosilicate molecular sieve 3, the composite palladium-based alloy material 2, and the support 1, thereby obtaining high-purity hydrogen; and further recovering and capturing the unreacted carbon dioxide.
[0075] The present invention will be described in detail below through examples. In the following examples and comparative examples, the inner surface of the support is sealed with polytetrafluoroethylene (PTFE) material, so molecular sieves, sodium-modified nano-Fe3O4, etc. are selectively loaded only on the outer surface of the support, and the PTFE material is peeled off before application or performance testing.
[0076] Examples E1-E4
[0077] (1) Using a porous stainless steel tube as the support (tubular, inner diameter: 10 mm, outer diameter: 13 mm; average pore size: 0.25 μm, porosity: 65%), the support was first soaked in anhydrous ethanol for 30 minutes to remove surface contaminants such as dust and grease. Then, the surface and inner side of the support were rinsed with deionized water and placed in warm water for vacuum cleaning to remove residual ethanol from the pores. Finally, it was placed in an oven and dried at 423 K for 4 hours. According to Faraday's law, Pd, Cu, and Ag atomic molar ratios M were deposited on the support using electroplating, as shown in Table 1. The effective film area was 50 cm². 2 The electroplating process involved using a conductive layer carrier as the working electrode, a platinum electrode (Pd plating), a waveguide with 99.999% copper content (Cu plating), and a silver electrode (Ag plating) as the counter electrodes, with a saturated calomel electrode as the reference electrode. The plating solution contained metal ions (Pd...) 2+ Cu 2+ Ag +The concentration was 0.01-0.1 mol / L. Electroplating experiments were carried out using cyclic voltammetry, with the working voltage range being -0.60V to -0.90V, the scan rate being 0.0075V / s, the scan period being 1000, and the sensitivity being set to 0.0001A / V. Meanwhile, during the electroplating process, a plunger-type constant flow pump was used to add the following solutions to the plating bath at a rate of 1-2 ml / min: 0.05 mol / L ammonium palladium chloride ((NH4)2PdCl4) solution; 0.5-1.5 ml / min: 0.075 mol / L copper nitrate (Cu(NO3)2) solution; 0.25-1 ml / min: 0.05 mol / L silver nitrate (AgNO3) solution; 0.1 ml / min: ethylenediamine (EDA, 99%, analytical grade); 0.05 ml / min: disodium ethylenediaminetetraacetate (EDTA-2Na, 99%, analytical grade); and 0.01 ml / min: bipyridine (C... 10 H8N2 (99%, analytical grade). The plating bath was vigorously stirred (1000 r / min) while the above solution was added. Every 30 min of electroplating, the working electrode, cleaned with distilled water, was immersed for 10 min in 0.05 mol / L phosphoric acid (H3PO4) solution and 0.05 mol / L dipotassium hydrogen phosphate (K2HPO4) solution, respectively. After the cyclic voltammetry procedure, the working electrode was treated in distilled water at 95℃ for 15 min before being removed. The Pd, Cu, and Ag deposited support was subjected to high-temperature alloying treatment. The alloying treatment was performed as follows: under an activating atmosphere, at temperature T1 and pressure P, for a period of time (t); then, the temperature was reduced to T2 at a cooling rate V. The activating atmosphere consisted of H2 and N2, with the volume ratio of H2 to N2 equal to R1. The amount of activating atmosphere gas provided ensured that the alloying pressure was P. Detailed parameters are shown in Table 1.
[0078] (2) The alloyed material obtained in step (1) was placed in the precursor solution of HZSM-5 molecular sieve for hydrothermal crystallization (aging and crystallization were performed in sequence), drying, calcination and ammonium exchange using ammonium nitrate (NH4NO3). The molar ratio R2 of silicon source, aluminum source, template agent and water and the conditions of each step are shown in Table 1 to obtain the composite membrane precursor. In the precursor solution of HZSM-5 molecular sieve, tetrapropylammonium hydroxide is used as template agent, tetrabutyl orthosilicate (TEOS) is used as silicon source and sodium aluminate is used as aluminum source. The amount of silicon-aluminum molecular sieve precursor solution used is 0.25 ml relative to 1 g of alloyed material.
[0079] The specific method of ammonium exchange is as follows: a 0.5 mol / L ammonium nitrate solution (NH4NO3) is used as the ion exchanger, according to Na... +Add 1.5 times the feed amount, immerse the calcined product to be exchanged into the above ion exchanger, and stir at 50 r / min for 2 h at 80 °C and normal pressure; dry the ion-exchanged sample in an oven at 100 °C for 6 h. Repeat the above operation once by immersing the dried sample into the above ion exchanger.
[0080] (3) Sodium-modified nano-Fe3O4 was deposited on the surface of the composite membrane precursor to obtain a composite membrane. The steps for depositing sodium-modified nano-Fe3O4 were as follows: a mixed solution of FeCl3 and FeCl2 was prepared using FeCl3·6H2O and FeCl2·4H2O in a molar ratio of 2. The pH was adjusted with 0.1 mol / L NaOH to obtain a solution containing iron and sodium sources. The mixture was stirred at a stirring rate of 500 r / min and aged to obtain an impregnation solution. The composite membrane precursor was then impregnated in the impregnation solution and dried at 25 °C and 0.002 MPa vacuum for 10 h to remove free water. Subsequently, it was calcined at 475 °C for 5 h to remove water of crystallization and template agent. The molar ratio of Na to Fe in the solution containing iron and sodium sources, R3 (as shown in Table 1), was 0.025 ml relative to 1 g of composite membrane precursor.
[0081] Table 1
[0082]
[0083] Example E5
[0084] The process was carried out in accordance with Example E1, except that the gas providing the activation atmosphere was changed to hydrogen and ammonia, with a volume ratio of 2.5:1, and the treatment time in the activation atmosphere was t = 4h.
[0085] Example E6
[0086] The process was carried out in accordance with Example E1, except that the gas providing the activation atmosphere was changed to hydrogen and hydrazine, with a volume ratio of 3:1, and the treatment time in the activation atmosphere was t = 3.5 h.
[0087] Example E7
[0088] The process was carried out in accordance with Example E1, except that the gas providing the activation atmosphere was changed to hydrogen and phosphine, with a volume ratio of 3.5:1, and the treatment time in the activation atmosphere was t = 1.5 h.
[0089] Example ED1
[0090] The process is carried out in accordance with Example E1, except that the gas providing the activating atmosphere is only N2.
[0091] Example ED2
[0092] The process is carried out in accordance with Example E1, except that the gas providing the activating atmosphere is only H2.
[0093] Example ED3
[0094] The process is carried out in accordance with Example E1, except that the gas providing the activation atmosphere is only argon.
[0095] Example ED4
[0096] The process is carried out in accordance with Example E1, except that the gases providing the activation atmosphere are hydrogen and CO2 (volume ratio 1:1).
[0097] Example ED5
[0098] The process was carried out in accordance with Example E1, except that the temperature was reduced to T2 at a rate of V = 5°C / min.
[0099] Example ED6
[0100] The process was carried out in accordance with Example E1, except that the alloying temperature T1 = 700°C.
[0101] Example ED7
[0102] The alloying process was carried out in accordance with Example E1, except that the alloying pressure P = 0.1 MPa.
[0103] Comparative Example 1
[0104] The procedure was carried out in accordance with Example E1, except that the molar ratio of Pd, Cu and Ag atoms was M = 100:500:500.
[0105] Comparative Example 2
[0106] The procedure was carried out in accordance with Example E1, except that the molar ratio of Pd, Cu, and Ag atoms was M = 100:0.5:0.5.
[0107] Test case
[0108] (I) The materials obtained after alloying treatment in step (1) of each embodiment and comparative example (i.e., composite palladium-based alloy materials) were characterized. The characterization method is as follows, and the crystal structure parameters of the composite palladium-based alloy materials are shown in Table 2.
[0109] The crystal structure analysis of the composite palladium-based alloy was performed on an X'Pert PRO / PANalytical automated X-ray diffractometer manufactured by Philips, Netherlands. The experimental conditions were Cu K αX-rays (λ = 0.1543 nm), tube voltage 40 kV, current 40 mA, diffraction angle 2θ scan range 10-90°. The interplanar spacing of the sample was calculated using the Bragg equation.
[0110] d=λ / 2sinθ
[0111] Where λ corresponds to Cu K α The wavelength of the radiation, θ is the angle of the diffraction peak.
[0112] The crystal structure of the composite palladium-based alloy was tested at the European Synchrotron Radiation Facility (beam BM25A) in France, which has higher resolution, with synchrotron radiation λ = 0.0618886 nm or 0.077449 nm and tube voltage of 10.0335 keV or 20.0335 keV. Initially, a 10 × 1 mm sample was used. 2 The sample was placed in a 2mm diameter quartz capillary tube, with both ends sealed with quartz wool. The capillary tube was then mounted on a rotating sample stage (to ensure uniform temperature and a larger X-ray irradiation area). The test temperature range was 298-473K (heated by a hot air blower), and the pressure range was 10... -4 The test atmosphere was -130 kPa. Hydrogen gas was first introduced and treated for 30 minutes, then a vacuum was drawn, and helium gas was introduced as a protective gas for measurement.
[0113] Methods for testing the lattice parameters of composite palladium-based alloy materials: Combining the above-mentioned in-situ XRD tests, the cell parameters of the palladium-based alloy materials are obtained (represented by three cell constants a, b, and c, and the three inter-edge angles α, β, and γ). According to the formula d1 = a / (α... 2 +β 2 +γ 2 ) 0.5 d2=b / (α) 2 +β 2 +γ 2 ) 0.5 d3=c / (α) 2 +β 2 +γ 2 ) 0.5The interplanar spacing (d1 d2 d3) of the corresponding characteristic crystal planes is calculated. That is, the PdCuAg alloy material obtained in this invention belongs to the face-centered cubic close-packed (FCC) structure, and its characteristic crystal planes include (110), (111), (220), (311), and (222). At the same time, according to the X-ray diffraction results, a series of different characteristic crystal plane ratios (the intensity corresponding to different crystal planes) can be obtained. For example, in the PdCuAg alloy material obtained in this invention, the (110) plane corresponds to the characteristic peak at 2θ = 40° ± 1°, the (111) plane corresponds to the characteristic peak at 2θ = 46° ± 1°, the (220) plane corresponds to the characteristic peak at 2θ = 69° ± 1°, the (311) plane corresponds to the characteristic peak at 2θ = 83° ± 1°, and the (222) plane corresponds to the characteristic peak at 2θ = 87° ± 1°. Using HighScorePlus analysis software, combined with the peak intensities of the aforementioned characteristic crystal planes, the lattice parameters k of the corresponding materials are calculated.
[0114] The thickness of the composite palladium-based alloy material was tested by scanning electron microscopy (model: JSM-7610F). The thickness of the alloy film was determined by measuring the corresponding scale according to the magnification. The surface smoothness of the obtained composite palladium-based alloy material could also be observed by scanning electron microscopy. The results showed that the surface of the palladium-based alloy material prepared by this invention was smooth and free of defects.
[0115] The method for testing the half-peak width (WHM) of composite palladium-based alloy materials is as follows: based on the XRD spectrum test results, combined with HighScore Plus software analysis, the radian value of the WHM is obtained.
[0116] (II) The composite membranes (materials obtained before loading sodium-modified nano-Fe3O4) obtained in each embodiment and comparative example were subjected to solid-phase exfoliation treatment to peel off the molecular sieves for characterization. The characterization method is as follows, and the relevant structural parameters of the molecular sieves attached to the surface of the composite palladium-based alloy material are obtained, as shown in Table 2.
[0117] The molecular sieve was analyzed using an Empyrean X-ray diffractometer from Malvern-Panalytical. The test conditions were: Cu target, Ka radiation, Ni filter, tube voltage 40 kV, tube current 40 mA, scintillation counter, step size 0.0131°, scan range 5–35°, and scan rate 2.5° / min. The results showed that it is an HZSM-5 silica-alumina molecular sieve with a double ten-membered ring cross-channel structure (MFI structure). Figure 2 The XRD pattern of the molecular sieve obtained in Example E1 is shown. The four characteristic peaks between 23° and 25° indicate that the material contains a double ten-membered ring cross-channel structure, which is consistent with the characteristics of HZSM-5 silica-alumina molecular sieve. The XRD patterns of the molecular sieves in each example are consistent with... Figure 2 Similarly, this indicates that the obtained molecular sieves are all HZSM-5 silica-alumina molecular sieves;
[0118] Methods for determining the specific surface area and average pore size of molecular sieves: The tests were conducted using a Micromeritics ASAP2020 physical adsorption instrument (USA). Samples were subjected to high vacuum treatment at 363 K and 573 K for 1 h and 3 h, respectively, followed by adsorption using N2 as the adsorbate at a constant temperature of 77 K. The BET specific surface area was obtained from the N2 adsorption isotherm combined with the BET equation; the average pore size was determined using the BJH method, calculated from the desorption branch of the N2 adsorption isotherm.
[0119] Method for testing the crystallinity of molecular sieves: A conventional X-ray diffractometer was used with a tube voltage of 40 kV, a tube current of 40 mA, and a scanning speed of 2.5° / min. The diffraction patterns of the samples were recorded within the range of 2θ = 5–35°. ZSM-5 sample M196697 from Shanghai Aladdin Biochemical Technology Co., Ltd. was used as a reference sample, with its relative crystallinity set to 100. The relative crystallinity of each sample was calculated by summing the peak intensities of its characteristic diffraction peaks at 2θ = 7.96°, 8.83°, 23.18°, 23.99°, and 24.45° and comparing this sum with the sum of the peak intensities of the reference sample.
[0120] The methods for testing the average particle size of molecular sieves are as follows: observe the microstructure of the molecular sieve in the sample using a transmission electron microscope and measure the diameter according to the scale bar; calculate the corresponding particle size distribution by taking the average of several samples using mathematical statistical methods.
[0121] The thickness of the molecular sieve loaded with Na-Fe3O4 nanoparticles was determined by scanning electron microscopy, and the thickness of the molecular sieve membrane loaded with Na-Fe3O4 nanoparticles was determined by measuring the scale corresponding to the magnification.
[0122] (III) Overall testing of composite membranes
[0123] E act (Hydrogen permeation activation energy, unit: kJ·mol) -1 The test method involves measuring the hydrogen permeation rate from 573 K to 773 K under a transmembrane pressure difference of 0.1 MPa, combined with the Arrhenius equation J. H2 =J H2 o exp(-E act / RT), calculated through measurement, where J H2 It is the hydrogen permeation diffusion rate, J H2 oR is the hydrogen permeation diffusion coefficient, T is the gas constant, and T is the absolute temperature. The higher the hydrogen permeation activation energy, the higher the hydrogen mass transfer resistance of the composite membrane material, and the more difficult it is for hydrogen to permeate and diffuse through the composite membrane.
[0124] J H2 (Hydrogen permeation diffusion rate, unit: mol·m) -2 ·s -1 The test method involves measuring the volume of hydrogen passing through the palladium-based composite membrane per minute (liters) at 20℃ and a transmembrane pressure difference of 0.1 MPa, and then normalizing it to the hydrogen permeation rate (mol·m²) based on the membrane area (square meters). -2 ·s -1 ).
[0125] J N2 (Nitrogen permeation diffusion rate, unit: mmol·m) -2 ·s -1 The test method involves measuring the volume (mL) of nitrogen gas passing through the palladium-based composite membrane per minute at 20℃ and a transmembrane pressure difference of 0.1 MPa, and then normalizing it to the hydrogen permeation rate (mmol·m²) based on the membrane area (m²). -2 ·s -1 ).
[0126] The elemental composition of the composite film was analyzed by X-ray fluorescence (XRF) combined with inductively coupled plasma optical emission spectroscopy (ICP-OES), and the valence states of the elements were determined by X-ray photoelectron spectroscopy (XPS).
[0127] The morphology of Na-Fe3O4 nanoparticles was observed using scanning electron microscopy (SEM), and the average particle size was calculated. Figure 3 The image shows a SEM image of the Na-Fe3O4 nanoparticles in the composite film obtained in Example E1.
[0128] The test results are shown in Table 2.
[0129] Table 2
[0130]
[0131]
[0132] Table 2 (continued)
[0133]
[0134] (IV) Application Testing
[0135] The performance of the composite membranes prepared in the above embodiments and comparative examples was tested in the capture of carbon dioxide before combustion and in the preparation of gasoline distillate hydrocarbons by carbon dioxide hydrogenation.
[0136] The composite membrane prepared above is encapsulated in a reactor for pre-combustion capture of carbon dioxide and the production of gasoline distillate hydrocarbons from carbon dioxide. For example... Figure 1 As shown, the composite membrane includes a support 1, a composite palladium-based alloy material 2, and an HZSM-5 silica-alumina molecular sieve layer 3 loaded with Na-Fe3O4 nanoparticles, sequentially attached to the support 1. The reactant gases (CO2 and H2) enter the membrane reactor and undergo a carbon dioxide hydrogenation reaction under the action of a catalyst (loaded with Na-Fe3O4 nanoparticles) to produce gasoline distillate hydrocarbons and some unreacted CO2. The remaining unreacted hydrogen gas passes sequentially through the HZSM-5 silica-alumina molecular sieve layer 3 loaded with Na-Fe3O4 nanoparticles, the composite palladium-based alloy material 2, and the support 1, and is purified to over 99.999% to obtain high-purity hydrogen gas, which is then used as a feedstock in a hydrogen fuel cell system. The specific operation is as follows: A mixture of methane reformed gas (CO2 and H2 in a volume ratio of 1:4, with a mixed gas volume hourly space velocity of 5000 h⁻¹) is introduced at 350°C and 0.3 MPa pressure. -1 The mixed gas was separated by a composite membrane, yielding pure hydrogen on the permeate side and a mixture of hydrogen and carbon dioxide on the residual side. Under the catalytic action of Na-Fe3O4 / HZSM-5 in the composite membrane, gasoline distillate hydrocarbons and some unreacted CO2 were obtained. The hydrogen product on the permeate side was analyzed online using a Shanghai Tianmei SCION-456 gas chromatograph equipped with FID and PDHID detectors to monitor hydrogen purity changes in real time. The components and relative contents of gasoline distillate hydrocarbons on the residual side were detected using an Agilent 7890B chromatograph equipped with TCD and FID detectors, and the percentage contents of unreacted hydrogen, carbon dioxide, and other raw materials were also detected. Based on the detection results, the carbon dioxide conversion rate, gasoline distillate hydrocarbon selectivity, and hydrogen recovery rate were calculated. The products were tested every 5 hours. The continuous operating time was recorded when the carbon dioxide conversion rate decreased to 90% of the initial value. The initial reaction values and experimental measurements after reaching the continuous operating time are shown in Table 3. The gasoline fraction hydrocarbons in the mixed components are enriched and absorbed by light naphtha absorbent. When the remaining CO2 concentration after the permeate side reaction is high enough, the carbon dioxide component is further enriched and sealed after compression.
[0137] Carbon dioxide conversion rate (C CO2 = Amount of carbon dioxide at reactor outlet / (Amount of carbon dioxide at reactor inlet - Amount of carbon dioxide at reactor outlet)
[0138] Gasoline fraction hydrocarbon selectivity (S gasline = Reactor outlet C5~C 12 The sum of the amounts of hydrocarbons / the total amount of hydrocarbons at the reactor outlet
[0139] Hydrogen recovery rate (R)H2 = Amount of hydrogen permeating through the osmotic side / Amount of hydrogen introduced into the reaction
[0140] Hydrogen-nitrogen selectivity (α(H2 / N2)) refers to the ratio between the hydrogen permeation / diffusion rate and the nitrogen permeation / diffusion rate at the defect site on the palladium film. A higher value indicates higher mechanical structural stability of the palladium film and fewer defects in the composite membrane material. Specifically, this is determined by measuring the hydrogen permeation / diffusion rate (J / N2) of the membrane. H2 The nitrogen permeation diffusion rate at the defect under the same conditions (573 K, 0.5 MPa transmembrane pressure difference) (J) N2 According to the formula α(H2 / N2)=J H2 / J N2 The above measurement methods were used to obtain the result.
[0141] Table 3
[0142]
[0143] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A palladium-based composite membrane comprising a silica-alumina molecular sieve, characterized in that, The composite membrane comprises a composite palladium-based alloy material and a silica-alumina molecular sieve loaded with sodium-modified nano-Fe3O4 attached to the surface of the composite palladium-based alloy material. The composite palladium-based alloy material is composed of Pd, Cu, and Ag, and the molar ratio of Pd, Cu, and Ag is 100:(12-38):(9-25). The crystal structure of the composite palladium-based alloy material is face-centered cubic close-packed, and the lattice parameter k is 0.4025-4255 nm. In the XRD pattern of the composite palladium-based alloy material, 2θ = 40° o ±1 o The full width at half maximum (FWHM) of the characteristic peak at that location is less than or equal to 0.0698, and 2θ = 46. o ±1 o The full width at half maximum (FWHM) of the characteristic peak at that location is less than or equal to 0.0873, and 2θ = 69. o ±1 o The full width at half maximum (FWHM) of the characteristic peak at that location is less than or equal to 0.1047, and 2θ = 83. o ±1 o The full width at half maximum (FWHM) of the characteristic peak at that location is less than or equal to 0.1396, and 2θ = 87. o ±1 o The full width at half maximum (FWHM) of the characteristic peak at that location is less than or equal to 0.1633. The crystal phase structure analysis of the composite palladium-based alloy material was performed using an X-ray diffractometer. The experimental conditions were Cu... K α ray, λ = 0.1543 nm, tube voltage 40 kV, current 40 mA, diffraction angle 2 θ The scanning range is 10-90. o ; The method for testing the half-peak width (WHM) of composite palladium-based alloy materials is as follows: based on the X-ray diffraction test results, combined with HighScore Plus software analysis, the radian value of the WHM is obtained.
2. The composite membrane according to claim 1, wherein, The thickness of the composite palladium-based alloy material is 0.5-30µm.
3. The composite membrane according to claim 1, wherein, The thickness of the composite palladium-based alloy material is 5-15µm.
4. The composite membrane according to claim 1, wherein, The composite membrane is a tubular membrane; And / or, the composite membrane further includes a support, on which the composite palladium-based alloy material is attached, and the thickness of the support is 0.1-20 mm.
5. The composite membrane according to claim 4, wherein, The thickness of the support is 2-5mm.
6. The composite membrane according to claim 1, wherein, The silica-alumina molecular sieve is at least one of HZSM-5, HZSM-11, HZSM-12, HZSM-23, HZSM-34, HY, HMCM-22, HBEA, and HMOR; And / or, the thickness of the silica-alumina molecular sieve loaded with sodium-modified nano-Fe3O4 is 100-3750 nm; And / or, the silica-alumina molecular sieve has a silica-alumina molar ratio of (2-50):1:1; an average particle size of 50-420 nm; an average pore size of 0.25-225 nm; and a specific surface area of 25-600 m². 2 / g; crystallinity greater than or equal to 92%.
7. The composite membrane according to claim 1, wherein, The thickness of the silica-alumina molecular sieve loaded with sodium-modified nano-Fe3O4 is 350-1500 nm.
8. The composite membrane according to claim 1, wherein, The silicon-aluminum molecular sieve has a silicon-aluminum molar ratio of (5-20):
1.
9. The composite membrane according to claim 1, wherein, The average particle size of the silicon-aluminum molecular sieve is 150-300 nm.
10. The composite membrane according to claim 1, wherein, The average pore size of the silica-alumina molecular sieve is 0.75-35 nm.
11. The composite membrane according to claim 1, wherein, The specific surface area of the silica-alumina molecular sieve is 50-500 m². 2 / g.
12. The composite membrane according to claim 1, wherein, The crystallinity of the silica-alumina molecular sieve is 96-99%.
13. The composite membrane according to claim 1, wherein, The average particle size of the sodium-modified nano-Fe3O4 is 5-300 nm; And / or, the loading of the sodium-modified nano-Fe3O4 is such that the molar ratio of Pd to Fe is 1:(0.001-0.1). And / or, the molar ratio of Na to Fe in the sodium-modified nano Fe3O4 is 1:(1-10).
14. The composite membrane according to claim 1, wherein, The average particle size of the sodium-modified nano-Fe3O4 is 10-100 nm.
15. A method for preparing a palladium-based composite membrane comprising a silica-alumina molecular sieve, characterized in that, The method includes: (1) Pd, Cu and Ag are deposited on the support, and then the support with Pd, Cu and Ag deposited is alloyed, wherein the molar ratio of Pd, Cu and Ag is 100:(12-38):(9-25). The alloying process is as follows: heat treatment is performed in an activating atmosphere at a temperature of 500-650°C and a pressure greater than 0.1 MPa, followed by cooling to below 200°C at a rate greater than 30°C / min. The activating atmosphere includes an alkaline gas; the content of the alkaline gas in the activating atmosphere is greater than or equal to 20% by volume; the alkaline gas is selected from at least one of ethylenediamine, NH3, PH3, and N2H4. (2) The alloyed material is placed in a solution of a precursor containing silicon-aluminum molecular sieve and subjected to hydrothermal crystallization, drying and calcination in sequence to obtain a composite membrane precursor; (3) Sodium-modified nano-Fe3O4 is loaded onto the surface of the composite membrane precursor.
16. The method according to claim 15, wherein, The alloying treatment is performed as follows: after treatment in an activating atmosphere at a temperature of 600-625℃ and a pressure of 0.56-0.73MPa for 1.5-7h, the temperature is reduced to 150-200℃ at a rate of 55-75℃ / min. And / or, the total thickness of Pd, Cu and Ag deposited on the support is 0.5-30µm; And / or, the thickness of the support is 0.1-20 mm.
17. The method according to claim 15, wherein, The total thickness of Pd, Cu and Ag deposited on the support is 5-15µm.
18. The method according to claim 15, wherein, The thickness of the support is 2-5mm.
19. The method according to claim 15, wherein, The precursor solution of the silicon-aluminum molecular sieve contains a silicon source, an aluminum source, a template agent, and water.
20. The method according to claim 19, wherein, The molar ratio of the silicon source, aluminum source, template agent, and water is 100:(2-50):(15-65):(60-2400). And / or, relative to 1g of alloyed material, the amount of the precursor solution containing silica-alumina molecular sieve is 0.025-0.85 ml; And / or, the silicon source is at least one of silicate ester, silicate and silicon dioxide; And / or, the aluminum source is at least one of aluminate, alumina, aluminum salt, aluminum sol, and organic aluminum alkoxide; And / or, the template agent is at least one of tetraalkylammonium hydroxide, alkylamine, and tetraalkylammonium halide.
21. The method according to claim 19, wherein, The molar ratio of silicon source, aluminum source, template agent, and water is 100:(5-20):(20-50):(70-1250).
22. The method according to claim 19, wherein, The silicon source is selected from at least one of tetrabutyl orthosilicate, tetraethyl orthosilicate, sodium silicate, potassium silicate, silica sol, and water glass.
23. The method according to claim 19, wherein, The aluminum source is selected from at least one of sodium aluminate, boehmite, aluminum sulfate, aluminum nitrate, and aluminum isopropoxide.
24. The method according to claim 19, wherein, The template agent is selected from at least one of tetrabutylammonium hydroxide, tetrapropylammonium hydroxide, tetraethylammonium hydroxide, triethylamine, hexadecyltrimethylammonium bromide, and isopropylamine.
25. The method according to claim 15, wherein, The hydrothermal crystallization method involves aging followed by crystallization. The aging conditions include an aging temperature of 70-90℃ and an aging time of 6-10 hours. The crystallization conditions include a crystallization temperature of 160-190℃ and a crystallization time of 24-48 hours. And / or, the drying conditions include: drying temperature 50-80℃, drying time 8-12h; And / or, the calcination conditions include: calcination temperature of 575-625℃ and calcination time of 4-6h.
26. The method according to claim 15, wherein, The method of loading sodium-modified nano-Fe3O4 onto the surface of the composite membrane precursor is as follows: the composite membrane precursor is impregnated with a solution containing iron source and sodium source, and then dried and calcined in sequence. The molar ratio of Na to Fe in the solution containing iron source and sodium source is 1:(1-10).
27. The method according to claim 26, wherein, The pH value of the solution containing iron and sodium sources is 8-12; And / or, relative to 1g of composite membrane precursor, the amount of solution containing iron and sodium sources is 0.01-0.05 ml; And / or, the iron source is selected from at least one of ferric salts and ferrous salts; And / or, the sodium source is selected from at least one of sodium hydroxide and sodium salts; And / or, the impregnation conditions include: an impregnation temperature of 15-85°C; and an impregnation time of 0.5-3.5 h; And / or, the calcination conditions include: a calcination temperature of 325-500℃ and a calcination time of 3-5h.
28. The method according to claim 26, wherein, The pH of the solution containing iron and sodium sources is 9-11.
29. The method according to claim 26, wherein, The iron source is at least one of FeCl3, FeCl2, Fe(NO3)3, FeSO4, NH4Fe(SO4)2, and (NH4)2Fe(SO4)2.
30. The method of claim 26, wherein, The sodium source is at least one of NaOH, NaHCO3, Na2CO3, and NaCl.
31. The method according to claim 26, wherein, The conditions for immersion include: immersion temperature of 25-60℃; immersion time of 1-2 hours.
32. The composite membrane prepared by the method according to any one of claims 15-31.
33. A composite palladium-based alloy material, characterized in that, The composite palladium-based alloy material is the composite palladium-based alloy material as defined in any one of claims 1-14 or the product of the alloying treatment described in step (1) of the method for preparing a palladium-based composite membrane comprising a silicon-aluminum molecular sieve as described in any one of claims 15-31.
34. The application of the composite membrane according to any one of claims 1-14 or 32 in carbon dioxide capture.
Citation Information
Patent Citations
Gold deposition process on surface of metal palladium and preparation of palladium alloy membrane
CN106381484A
Surface nitrogen-containing nickel-based alloy loaded catalyst and preparation and application
CN109225295A
